1986
DOI: 10.1002/1097-0142(19860215)57:4<779::aid-cncr2820570417>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

CA 19-9 and pancreatic adenocarcinoma

Abstract: The diagnostic place value of CA 19-9, a tumor-associated antigen, was tested in 611 patients. This group of patients included 273 patients who suffered from a malignant disease (48 patients with pancreatic carcinomas and 225 patients with extrapancreatic malignant growths) and 338 patients with benign diseases (66 patients with chronic pancreatitis, 36 patients with acute pancreatitis, and 236 patients with general surgical diseases). In 93% of the patients with pancreatic carcinoma (media value, 528 U/ml), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 6 publications
2
37
0
2
Order By: Relevance
“…9,10 Although the tumor-associated antigen CA 19-9 was initially described as a marker for colorectal cancer, 11 it later became vident that its most important clinical applications are related to pancreatic cancer. 12, 13 Since then, CA 19-9 is recognized as the first tumor marker that successfully aids in the diagnosis of pancreatic cancer with reported sensitivity of 68%-94% and specificity of 76%-100%. 14 The CA 19-9 monoclonal antibody has as its epitope the blood group carbohydrate antigen sialyl Lewis[a].…”
mentioning
confidence: 99%
“…9,10 Although the tumor-associated antigen CA 19-9 was initially described as a marker for colorectal cancer, 11 it later became vident that its most important clinical applications are related to pancreatic cancer. 12, 13 Since then, CA 19-9 is recognized as the first tumor marker that successfully aids in the diagnosis of pancreatic cancer with reported sensitivity of 68%-94% and specificity of 76%-100%. 14 The CA 19-9 monoclonal antibody has as its epitope the blood group carbohydrate antigen sialyl Lewis[a].…”
mentioning
confidence: 99%
“…Multiple studies have shown that while elevations in serum CA 19-9 is useful in the diagnosis of adenocarcinoma of the upper gastrointestinal tract and in monitoring of colonic carcinoma, its greatest sensitivity is in the detection of pancreatic adenocarcinoma (24).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…If elevated, this tumor marker has proved to be a highly sensitive indication of tumor cells remaining after pancreatic resection. 44,45 There are several reasons that may explain the negative outcome of this trial. It could be that the dosage used is too low to adequately saturate the target e p i t~p e s .~~ In other clinical trials making claims about the effects of murine MoAb in gastrointestinal tumors, the dosages used were in part higher than the total dose of 370 mg used in this trial.…”
Section: Discussionmentioning
confidence: 99%